Covalent 2D-Engineering of Graphene by Spatially Resolved Laser Writing/Reading/Erasing - Edelthalhammer, Konstantin; Dasler, Daniela; Jurkiewicz, Lisa; Nagel, Tamara; Al-Fogra, Sabrin; Hauke, Frank; Hirsch, Andreas; Al-Fogra, Sabrin (Angewandte Chemie International Edition, 2020)
We report a facile and efficient method for the covalent 2D-patterning of monolayer graphene via laser irradiation. We utilized the photo-cleavage of dibenzoylperoxide (DBPO) and optimized the subsequent radical additions to non-activated graphene up to that level where controlled covalent 2D-patterning of graphene initiated by spatially resolved laser writing is possible. The covalent 2D-functionalization of graphene, which is monitored by scanning Raman microscopy (SRM) is completely reversible. This new concept enables write/read/erase control over the covalent chemical information stored on the graphene surface.
CRIS-Team Scopus Importer:2020-10-16
Keywords: covalent functionalization; covalent patterning; graphene; Raman spectroscopy; write/read/erase

Sequential Tether-Directed Synthesis of New [3:2:1] Hexakis-Adducts of C-60 with a Mixed Octahedral Addition Pattern - Wachter, Michael; Jurkiewicz, Lisa; Hirsch, Andreas (Chemistry - A European Journal, 2021)
A new concept for the regioselective synthesis of [3 : 2 : 1] hexakis-adducts of fullerene C-60 was developed. Based on sequential tether-directed remote functionalizations, chiral [3 : 2] pentakis-adducts with an incomplete octahedral addition pattern were synthesized via stepwise cyclopropanation of C-60 with suitable macrocyclic tri- and bifunctional cyclomalonate tethers. The four resulting stereoisomers were isolated using chiral HPLC. The corresponding pairs of enantiomers show mirror image behavior in their CD-spectra. The pentakis-adducts served as suitable building blocks for the spatially controlled synthesis of mixed hexakis-adducts. Implementation of functional group-bearing monomalonates afforded octahedral [3 : 2 : 1] hexakis-adducts suitable for the construction of larger molecular and supramolecular fullerene architectures in excellent yield.
CRIS-Team Scopus Importer:2021-05-07
Keywords: cyclopropanation; exohedral functionalization; fullerenes; functional organic materials; regioselectivity

Spatially Resolved Janus Patterning of Graphene by Direct Laser Writing - Al-Fogra, Sabrin; Yang, Bowen; Jurkiewicz, Lisa; Hauke, Frank; Hirsch, Andreas; Wei, Tao (Journal of the American Chemical Society, 2022)
Covalently patterned Janus-functionalized graphene featuring a spatially defined asymmetric bifacial addend binding motif remains a challenging synthetic target. Here, a facile and universal laser writing approach for a one-step covalent Janus patterning of graphene is reported, leading to the formation of up to now elusive graphene architectures, solely consisting of antaratopically functionalized superlattices. The structurally defined covalent functionalization procedure is based on laser-triggered concurrent photolysis of two different photosensitizers situated on both sides of the graphene plane, generating radicals and subsequent addend binding in the laser-irradiated areas only. Careful structure analysis was performed by Raman spectroscopy and Kelvin probe force microscopy. In terms of the advantages of our newly established concept, including a simple/easy-to-operate patterning procedure, arbitrary pattern availability, and a high degree of addend binding, an easy access to tailor-designed Janus-functionalized graphene devices with spatially resolved functional entities can be envisaged.
CRIS-Team Scopus Importer:2022-11-04